Pengaruh DPK, Pembiayaan, dan NPF Terhadap Laba Bank Syariah Indonesia: Pendekatan Regresi Nonlinier - Muhammad Fauzan; Isra Misra; Puteri Pekerti Wulandari; Violeta Mardlatillah Romadoni Nur Indraswari; Miya Nanda Saputri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the effect of Third Party Funds (TPF), Financing, and Non-Performing Financing (NPF) on the profit of Bank Syariah Indonesia (BSI) using a nonlinear regression approach. The research employs a quantitative explanatory method with secondary quarterly data from BSI financial statements covering the period 2021Q1–2025Q3, totaling 19 observations. All variables are transformed into natural logarithms and estimated using the Ordinary Least Squares (OLS) method to capture potential nonlinear relationships among variables. The results indicate that financing has a positive and statistically significant effect on BSI’s profit, confirming its central role in supporting the bank’s profitability through margin and profit-sharing income. Meanwhile, Third Party Funds and Non-Performing Financing show no statistically significant effect on profit, although their coefficient signs are consistent with theoretical expectations. The coefficient of determination demonstrates that the model has strong explanatory power, and the overall model is statistically feasible. These findings suggest that BSI’s profitability is more strongly determined by the effectiveness and quality of financing distribution rather than merely the volume of funds collected or the level of problematic financing. The study contributes to the Islamic banking literature by providing empirical evidence on nonlinear relationships among intermediation variables and offers managerial implications for optimizing financing strategies while maintaining prudent risk management.